Analisis Cemaran Logam Berat Timbal (Pb) Dalam Kerang Darah (Anadara granosa) dan Kerang Patah (Meretrix lyrata) di Muara Angke Menggunakan Spektrofotometer Serapan Atom - Nadiah Ayu Nur (Poltekkes Kemenkes Bandung, 2017)
ABSTRAK : Heavy metal pollution of waters by oceans where place biota live is very dangerous because that consumed by many people. One of types biota that utilized because a large population as a food ingredients that is favored by the public is the blood shell (Anadara granosa) and white clam (Meretrix lyrata). Contamination of heavy metals in shell that commonly consumed by Indonesian people may cause various health problems. The study aimed to determine levels of lead (Pb) in blood shell (Anadara granosa) and white clam (Meretrix lyrata) from Muara Angke were analyzed by Atomic Absorption Spectrophometry (AAS) at specific wavelength, which 283,3 nm. Results this search showed that blood shell contained lead 1,1267; 0,0939; 0,4692 µg/g wet weight, and white clam 0,8450; 0,4883; 0,7323 µg/g wet weight. Under the regulation set by Badan Standarisasi Nasional 2009, lead levels in blood shell (Anadara granosa) and white clam (Meretrix lyrata) is still viable to consumed and have not crossed the line safely determined by BSN 2009 for this type of kekerangan i.e. 1.5 µg/g.Keywords : Lead, blood shell, white clam, Muara Angke, Atomic Absorption Spectrophotometer.